2019
DOI: 10.1111/1756-185x.13508
|View full text |Cite
|
Sign up to set email alerts
|

A low perfusion‐metabolic mismatch in 99mTl and 123I‐BMIPP scintigraphy predicts poor prognosis in systemic sclerosis patients with asymptomatic cardiac involvement

Abstract: Aim:This study investigated the prognostic factors of cardiac death or cardiac failure using cardiac scintigraphy, echocardiography (UCG), and magnetic resonance imaging (MRI) in asymptomatic systemic sclerosis (SSc) patients. Methods:We retrospectively evaluated SSc patients who had undergone cardiac scintigraphy using 99m thallium ( 99m Tl) and 123 I-β-methyl-P-iodophenyl-pentadecanoic acid ( 123 I-BMIPP), UCG, and cardiac MRI. We calculated the mismatch score in scintigraphy by subtracting the uptake of 123… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Our study revealed that CKD progression was frequent in patients to the underlying cardiac involvement of CTDs. [26][27][28][29][30][31][32] Recent studies have shown that a large part of the increase in pulmonary arterial pressure in patients with CTD-PH is attributed to impairment of the left ventricle. 33,34 Although we did not investigate the increase in post-capillary pressures on RHC at diagnosis, further analysis using exercise echocardiography or with the fluid challenge may reveal the underlying contribution of LV impairment in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that CKD progression was frequent in patients to the underlying cardiac involvement of CTDs. [26][27][28][29][30][31][32] Recent studies have shown that a large part of the increase in pulmonary arterial pressure in patients with CTD-PH is attributed to impairment of the left ventricle. 33,34 Although we did not investigate the increase in post-capillary pressures on RHC at diagnosis, further analysis using exercise echocardiography or with the fluid challenge may reveal the underlying contribution of LV impairment in this study.…”
Section: Discussionmentioning
confidence: 99%